2022
DOI: 10.1155/2022/4164824
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC3 Inhibition Alleviates High-Glucose-Induced Retinal Ganglion Cell Death through Inhibiting Inflammasome Activation

Abstract: Purpose. The exact effects of histone deacetylase 3 (HDAC3) inhibition in DR related retinal ganglion cells (RGCs) death remained unclear. This study is aimed at detecting the influence of HDAC3 on the high-glucose-induced retinal ganglion cell death. Methods. The retinal HDAC3 expression in DR of different time points was analyzed by immunohistochemical assay and western blot. Besides, the expression of HDAC3 and both retinal thickness and RGC loss were analyzed. The effects of HDAC3 inhibitor on cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%